2009
DOI: 10.1080/14488388.2009.11464801
|View full text |Cite
|
Sign up to set email alerts
|

Managing Spatial and Temporal Variability in Irrigated Agriculture Through Adaptive Control

Abstract: Spatial variability in crop production occurs as a result of spatial and temporal variations in soil structure and fertility; soil physical, chemical and hydraulic properties; irrigation applications; pests and diseases; and plant genetics. It is argued that this variability can be managed and the efficiency of irrigation water use increased by spatially variable application of irrigation water to meet the specific needs of individual management zones (areas of crop whose properties are relatively homogenous).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The results of this study show substantial accuracy advantages of continuous monitoring systems for PWW application. Automated irrigation systems are in development for surface gravity irrigation systems and have the potential to address water use efficiency and uniformity challenges in addition to fertigation management (Bali et al., 2018; Koech et al., 2010; Smith et al., 2009). Electrical conductivity proxy is one of several instantaneous N content measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study show substantial accuracy advantages of continuous monitoring systems for PWW application. Automated irrigation systems are in development for surface gravity irrigation systems and have the potential to address water use efficiency and uniformity challenges in addition to fertigation management (Bali et al., 2018; Koech et al., 2010; Smith et al., 2009). Electrical conductivity proxy is one of several instantaneous N content measurements.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, closed-loop control systems measure the output of a process (feedback, measured response) resulting in periodic adjustments to the controlled parameters during the process in order to minimize the differences between a measured response and the desired response. These types of systems are often referred to as closed-loop or adaptive control systems and have the flexibility to change control parameters to adjust for changing conditions in space and time depending on the feedback mechanisms and limitations (Smith et al, 2009). Closed-loop adaptive control systems are not used with any precision agriculture technology other than site-specific sprinkler irrigation.…”
Section: Site-specific Control Systemsmentioning
confidence: 99%
“…For instance, a study of Mutorahuku irrigation scheme showed that approximately 8m /hr of water was lost due to damaged canals [6]. is is further exacerbated by the observation that irrigators assume that the water requirement of each plant across a eld is the same and ignore di erences in crop water requirements due to spatial factors, which include plant genetics, soil type, and topography [7][8][9], resulting in a blanket application of water. Such anecdotes give credence to the need to improve water use efficiency in smallholder irrigation systems [10,11].…”
Section: Introductionmentioning
confidence: 99%